PEMBERIAN ASI DAN KEJADIAN IKTERUS PADA BAYI BARU LAHIR USIA 0-7 HARI: Pemberian ASI, Ikterus, Bayi - Puspita, Sylvie; Zihni Zatihulwani, Eliza (LPPM STIKES HUSADA JOMBANG, 2023)
Jaundice is a condition of the appearance of a yellow color in the skin and eye membranes in newborns due to the presence of bilirubin (bile pigment) in the skin and eye membranes as a result of increased levels of bilirubin in the blood. Breast milk is the main source for babies in their life. Babies can become yellowish or icterus if the frequency of breastfeeding is not suitable for the baby's needs. The purpose of this study was to determine the relationship between breastfeeding and the incidence of jaundice in newborns 0-7 from the Regional General Hospital dr. R. Soedarsono Pasuruan City. This research method is analytic with a cross sectional approach. The sampling technique is purposive sampling with a population of 48 respondents, a sample of 34 respondents. This research was carried out during on July 2022. Data collection was carried out by distributing questionnaires, then statistically tested using the spearman test using the SPSS for windows program with a limit of significance (α = 0.05) Ho was rejected if p value > 0.05 and Ha is accepted if p value < 0.05. The results showed that the majority of 34 respondents were in the category of frequent breastfeeding, negative jaundice, as many as 22 respondents (64.7%) and the positive category experiencing jaundice not often breastfeeding, as many as 12 respondents (35.3%). In conclusion, there is a relationship between breastfeeding and the incidence of jaundice in newborns 0-7 days.